The BoxTrolls - Snow, Alan; Morgan, Tracy, 1968-.; Collette, Tony; Frost, Nick, 1970-; Harris, Jared, 1961-; Fanning, Elle; Kingsley, Ben, 1943-; Hempstead, Isaac (Universal City, Ca Universal Studios Home Entertainment, 2015)
A community of quirky, mischievous creatures who have lovingly raised an orphaned human boy named Eggs in the amazing cavernous home they've built beneath the streets of Cheesebridge. When the town's villain, Archibald Snatcher, comes up with a plot to get rid of the Boxtrolls, Eggs decides to venture above ground, 'into the light,' where he meets and teams up with fabulously feisty Winnie. Together, they devise a daring plan to save Eggs' family.
Rated PG.
Based on the children's novel 'Here Be Monsters' by Alan Snow.
Bonus features: Dare to be Square: behind the scenes of The boxtrolls; 5 featurettes that take you inside the magical world of The Boxtrolls; feature commentary with directors Graham Annable and Anthony Stacchi.
Voices: Isaac Hempstead Wright, Ben Kingsley, Elle Fanning, Jared Harris, Nick Frost, Toni Collette, Tracy Morgan.
111725
Keywords: Families -- Juvenile films; Orphans -- Juvenile films; Trolls -- Juvenile films; Video recordings for the hearing impaired; Children's films; Animated films; Action and adventure films; Comedy films; Fantasy films